Etiology of the mango stem bark blackening in Sri Lanka and in vitro biocontrol assays - Herath, K.; Thiruchchelvan, N.; Manike, N.; Jayaprada, T.; Kumara, A. (Oxford University Press, 2025)
Mango (Mangifera indica ) is an economically significant fruit crop in Sri Lanka. Recently, a new disease, stem bark blackening, emerged on mango in the country, causing concerns among growers. This study aimed to identify the pathogen and explore effective in vitro strategies for its management. Field observations revealed characteristic black, irregularly shaped patches encircling the mango stems and branches. Morphological studies and phylogenetic analysis of the ITS region confirmed the pathogen as Aspergillus spp. In vitro assays demonstrated 92.4% fungal inhibition by Trichoderma viride. Among the tested plant extracts, Azadirachta indica showed the highest antifungal activity (72.3% colony size reduction compared to control). Commercial fungicides tested were less effective. In vitro biocontrol activity of T. viride and A. indica extract is more effective than conventional fungicides, highlighting their potential in integrated disease management of mango stem bark blackening disease.
Keywords: Fungicide; Growth inhibition; Mango; Neem; Stem bark blackening disease; Trichoderma